Public awareness of the bone morphogenic protein controversy: Evidence from news publications - Drazin, Doniel (Surg Neurol Int, 2014)
BACKGROUND: Use of recombinant human bone morphogenic protein-2 (rhBMP-2) in spinal fusion has seen a tremendous increase. Public awareness of rhBMP-2 and its complications has not been assessed. The authors studied published news media articles to analyze information provided to the public on this bone graft substitute. METHODS: We utilized the academic database, LexisNexis, to locate newspaper articles published between January 2001 and July 2013. All articles were coded by a coder and reviewed by the principal investigator. RESULTS: The search identified 87 national and 99 local newspaper articles. Complications mentioned in national newspapers included cancer (24%), retrograde ejaculation (24%), and abnormal bone growth (14%). Local newspapers cited cancer (14%), inflammation (14%), and retrograde ejaculation (9.2%) most frequently. Fifty national (59%) and 35 local (54%) articles had no mention of complications. Sources of evidence cited by articles were (in order of frequency): Governmental agencies, medical research or published studies, healthcare personnel or patients, and companies or corporations. CONCLUSIONS: Only a small percentage of newspaper articles presented potential complications. Despite lack of clear scientific causal relationship between rhBMP-2 and cancer, this risk was disproportionately reported. Additionally, many did not cite scientific sources. Lack of reliable information available to the public reiterates the role of physicians in discussing risks and benefits BMP use in spinal surgery, assuring that patients are making informed decisions. Future news media articles should present risks in an impartial and evidence-based manner. Collaboration between advocacy groups, medical institutions, and media outlets would be beneficial in achieving this goal.